2019
DOI: 10.3390/en12040578
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Bioenergy on Sustainable Economic Development

Abstract: The Solow-Swan macroeconomic model reveals the fact that the marginal capital rate of the bioenergy sector, as well as the bioenergy productivity and productivity of the resources variation, having positive values of their estimated coefficients, have the capacity of stimulating the sustainable economic development of an emerging country, such as Romania. The economic model substantiated by the correlations between the macroeconomic indicators evaluates the convergence in relation with the European Union (EU) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…The results of the study validate the statistical hypotheses that renewable energy, energy productivity, population, urbanization, motorization, and GDP per capita have a strong effect on carbon emissions. This confirms recent studies [34][35][36][37] that state that increasing levels of population and urbanization are leading to higher rates of carbon emissions.…”
Section: Discussion Of the Resultssupporting
confidence: 90%
“…The results of the study validate the statistical hypotheses that renewable energy, energy productivity, population, urbanization, motorization, and GDP per capita have a strong effect on carbon emissions. This confirms recent studies [34][35][36][37] that state that increasing levels of population and urbanization are leading to higher rates of carbon emissions.…”
Section: Discussion Of the Resultssupporting
confidence: 90%
“…Moreover, while some researchers [15][16][17] argue that the use of biofuels and bioenergy have a strong impact on the reduction levels of CO 2 , other economists [18][19][20] conclude that resources productivity and energy efficiency have a higher impact on CO 2 emissions. Nevertheless, while some authors [21][22][23] argued that bioenergy productivity and biofuel production have a direct and significant impact on decreasing the levels of CO 2 emissions, other researchers [24,25] concluded that population and urbanization levels have a significant and negative impact on decreasing the levels of CO 2 emissions. An assessment [24] of the European renewable energy source (RES) trajectory towards 2020, starting from historical values and through common scientific methods, laid down a new approach to evaluate RES performance in Europe.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The proposed framework is based on three indicators: the share of energy from RESs in gross final energy consumption, RES primary production per capita and the gross final consumption of RES per capita. Other researchers [25] analyzed the financial issues that might prevent the investment decisions of green companies. Their conclusions indicate that effective policy interventions should ensure that objectives are orientated towards the long term with the aim of reducing the risks perceived by financial institutions in funding biomass producers.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Another classification refers to voluntary or involuntary food waste depending on the cause that has led to the discarded food. Another categorization refers to avoidable, possibly avoidable and unavoidable food waste depending on the possibility of reusing the food material [31,32]. Besides the different types of food waste, it is also important to analyze the factors that favor or inhibit this phenomenon.…”
Section: Definition Of Food Wastementioning
confidence: 99%
“…According to a study conducted by Gustavsson et al (2011), the amount of wasted food is 12 times higher in industrialized countries compared to developing countries [19,33]. The climate and the availability of agricultural production [32] are also factors affecting food waste. For instance, more food is wasted in the summer [1], probably because of the fact that food is quicker to perish in warm temperatures.…”
Section: Factors Affecting the Waste Of Foodmentioning
confidence: 99%